Characteristics of health-related quality of life and related factors in patients with brain tumors treated with rehabilitation therapy - Takahiro Watanabe; Shinichi Noto; Manabu Natsumeda; Shinji Kimura; Satoshi Tabata; Fumie Ikarashi; Mayuko Takano; Yoshihiro Tsukamoto; Makoto Oishi (SpringerOpen, 2022)
Abstract Background Rehabilitation therapy during hospitalization is effective in improving activities of daily living (ADL) and physical function in patients with brain tumors. However, there are few studies on the effect of rehabilitation therapy on health-related quality of life (HRQOL) in patients with brain tumors. Additionally, the EuroQol-5Dimension-5Level (EQ-5D-5L) index score has not been reported as an outcome. This study aimed to investigate the HRQOL of patients with brain tumors who underwent rehabilitation therapy and investigated the factors affecting the EQ-5D-5L index score from various perspectives, including various brain tumor type and recurrence. In addition, we examined the relationship between the EQ-5D-5L index score, disease-specific HRQOL scale, and ADL. Methods Patients with brain tumors who underwent treatment and rehabilitation at Single tertiary care academic medical center were included in this cross-sectional study. We used the EQ-5D-5L, European Organisation for Research and Treatment of Cancer (EORTC) quality of life questionnaire core 30, and EORTC quality of life questionnaire brain cancer module to evaluate HRQOL. ADL were assessed using the functional independence measure (FIM). The relationship between each HRQOL assessment score and the FIM was analyzed, and the influence of related factors was assessed by multiple regression analysis. Results This study included 76 patients. The EQ-5D-5L index score was 0.689 for all patients with brain tumors and 0.574 for those with glioblastomas, which was the lowest value. There was a moderate correlation between the EQ-5D-5L index score and FIM (r = 0.627, p < 0.001). In addition, the EQ-5D-5L index score was significantly correlated with most of the items of the disease-specific HRQOL scale. Multiple regression analysis revealed that glioblastoma histology (coefficient: − 0.373, p = 0.005) and recurrence (coefficient: − 0.273, p = 0.020) were independent factors affecting the EQ-5D-5L index score. Conclusions Patients with glioblastoma undergoing rehabilitation have reduced HRQOL, which was influenced by glioblastoma histology and recurrence.